From Research to Clinical Practice: Long-Term Impact of Randomized Clinical Trial Examining the Effect of Lumbar Drains on Cerebrospinal Fluid Leak Rates Following Endonasal Skull Base Surgery - Lavigne, Philippe; Wang, Eric W.; Gardner, Paul A.; Snyderman, Carl H. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Intraoperative cerebrospinal fluid (CSF) leaks are associated with increased risk of postoperative CSF leaks despite multilayered reconstruction with vascularized tissue. A recent randomized controlled trial (RCT) examining the use of perioperative lumbar drains (LD) in high-risk skull base defects identified a significant reduction in postoperative CSF leak incidence (21.2 vs. 8.2%; p = 0.017). This study was conducted to assess the efficacy of the selective use of CSF diversion, for patients with intraoperative CSF leaks involving endoscopic endonasal approaches (EEA) to the skull base.Method Consecutive endoscopic endonasal surgeries of the skull base from a pre-RCT cohort and post-RCT cohort were compared. The following case characteristics between the two cohorts were examined: patient age, body mass index (BMI), rate of revision surgery, tumor histology, use of CSF diversion, and vascularized reconstruction. The primary measured outcome was postoperative CSF leak.Results The pre-RCT cohort included 76 patients and the post-RCT cohort included 77 patients, with dural defects in either the anterior or posterior cranial fossa (pituitary and parasellar/suprasellar surgeries excluded). There was a significant reduction in the incidence of postoperative CSF leak in the post-RCT cohort (27.6 vs. 12.9%; p = 0.04). On subgroup analysis, there was a trend toward improvement in CSF leak rate of the anterior cranial fossa (19.2 vs. 10.5%; p = 0.27), whereas CSF leak rates of the posterior cranial fossa were significantly reduced compared with the pre-RCT cohort (41.4 vs. 12.8%; p = 0.02).Conclusion This study demonstrates that the integration of selective CSF diversion into the reconstructive algorithm improved postoperative CSF leak rates.
Keywords: cerebrospinal fluid; skull base reconstruction; lumbar drain; skull base surgery